Contribution to the knowledge of Pyraloid moths (Lepidoptera, Pyraloidea) from the Andaman and Nicobar Islands, India - B. Sumit Kumar Rao; Chandrakasan Sivaperuman (Journal of Insect Biodiversity and Systematics)
The Andaman and Nicobar Islands, a biodiversity hotspot in India, hosts a diverse array of insect species, many of which are endemic to the region. The present work focuses on the pyraloid moth diversity in the Andaman and Nicobar Islands and significantly expands the knowledge of the known pyraloid moth fauna of the Andaman and Nicobar Islands, reporting new distributional records for 19 species. The work provides differential diagnoses, distributional data, and microphotographs of adult genitalia, including the first descriptions of genitalia structures for five species, namely Tatobotys varanesalis (Walker, 1859); Ravanoa xiphialis (Walker, 1859); Nosophora albiguttalis Swinhoe, 1890; Nosophora conjunctalis Walker, 1866; and Macaretaera hesperis Meyrick, 1886. Additionally, the documentation of seven genera new to the archipelago, viz. Macaretaera Meyrick, 1886; Ravanoa Moore, 1885; Bocchoris Moore, 1885; Botyodes Guenée, 1854; Hemopsis Kirti & Rose, 1987; Zitha Walker, 1866 and Termioptycha Meyrick, 1889, highlights the biogeographic significance of this underexplored region and the need for continued faunistic surveys.